PATHOMORPHOLOGICAL ASPECTS OF THE DEVELOPMENT OF BILIARY REFLUX AFTER MINI-GASTRIC BYPASS - A. G. Khitaryan; A. E. Neimark; A. V. Mezhunts; O. B. Starzhinskaya; A. A. Orekhov; O. V. Voronova; I. P. Chumburidze; M. Y. Shtilman; D. A. Melnikov (Вестник хирургии имени И.И. Грекова)
INTRODUCTION. MGB is considered to be the best alternative to Roux-en-Y gastric bypass (RYGB) due to the shorter operation time and fewer possible complications. The OBJECTIVE of this study was to determine biliary reflux in patients undergoing MGB with a hand-sewn gastroenteroanastomosis, and MGB with a stapler gastroenteroanastomosis.MATERIAL AND METHODS. This study included the analysis of results of treatment of 122 patients with morbid obesity and metabolic syndrome who had undergone laparoscopic MGB. Patients were divided into two clinical groups depending on the method of applying gastroenteroanastomosis. Clinical and endoscopic assessment was used to determine bile reflux; biliary reflux index (BRI) was used. In the postoperative period, the possibility of developing biliary reflux using fibrogastroscopy with biopsy of the gastric mucosa, microscopy of biopsy materials was evaluated. Microscopy of biopsy specimens was performed by a pathologist who evaluated each sample of gastric tissue in accordance with the system for determining the biliary reflux index (BRI).RESULTS. During fibrogastroscopy, biliary reflux was diagnosed in 9 (15.5 %) cases in the study group and 16 (26.6 %) cases in the control group. In the study group of patients, biliary reflux index (BRI) > 14 was determined in 3 patients (5.153 %). In the control group of patients, BRI> 14 was in 7 cases (10.94 %). The difference was significant (p<0.05).CONCLUSION. Determination of BRI index in patients undergoing MGB could be used as a screening method for diagnosing the biliary reflux in order to prevent and develop the tactic for further management of patients from a risk group of complications associated with the toxic effects of an aggressive bile refluxate.The authors declare no conflict of interest.The authors confirm that they respect the rights of the people participated in the study, including obtaining informed consent when it is necessary, and the rules of treatment of animals when they are used in the study. Author Guidelines contains the detailed information.